Albanian Mobile Companies 4G Service Strategies Application - Gjoni, Mario (British Journal of Marketing Studies, 2020)
Albanian mobile market is made of three big players. In this paper the strategies and application for the 4G services of all the operators is discussed and compared. Main point which is tested and discussed in this paper is the quality of service offered by all operators according to their respective clients relative to the application of the strategies pertaining to mobile internet services, and in particular 4G and 4G+ services. The data is organized and gathered according to the SERVQUAL model and his paper is only one piece of a bigger study made in Albanian Telecommunications’ Market. Primary data is analyzed using SPSS. The findings are true and representative of the Albanian market, according to the validity test and the findings.